Analysis of Prognostic Factors Affecting the Outcome of Stage IB-IIB Cervical Cancer Treated by Radical Hysterectomy and Pelvic Lymphadenectomy. (December 2016) - Xia, Xi; Xu, Hongbin; Wang, Zhonghai; Liu, Ronghua; Hu, Ting; Li, Shuang
Abstract : Objectives: The aim of this study was to identify the risk factors predicting the prognosis of patients with early-stage cervical cancer and to evaluate the effect of adjuvant therapy in patients with certain risk factors. Methods: The study population consisted of 274 patients who were presented with FIGO stage IB-IIB cervical cancers. They all received radical hysterectomy (type III) and systematic pelvic lymphadenectomy in our institute. Of the patients, 188 received postoperative adjuvant therapy including radiotherapy, chemotherapy, and chemotherapy plus radiotherapy. Radiotherapy was performed with a total of 50 Gy of external whole pelvic irradiation. Remote after loading of intravaginal iridium-192 brachytherapy were placed 1 to 2 weeks after completion of external RT. Chemotherapy was operated with 4 to 6 courses of platinum-based treatment. Chemotherapy plus radiotherapy was performed with the combination of periodically sequential chemotherapy and radiotherapy. Results: Univariate analysis revealed clinical stage, parametrial invasion, and pelvic node metastasis affected patients' disease-free (DFS) and overall survival (OS) rates, whereas multivariate analysis demonstrated parametrial invasion and pelvic node metastasis were independent risk factors for DFS and OS rates. Further analyses showed that adjuvant therapy could significantly enhance DFS and OS rates in patients without the above independent risk factors. Conclusions: Patients with combination of pelvic node metastasis and parametrial invasion have the poorest prognosis, and adjuvant therapy significantly increases DFS and OS rates among patients without parametrial invasion and pelvic node metastasis.